PERSEPSI MAHASISWA TERHADAP PEMBELAJARAN ONLINE SELAMA PANDEMI COVID-19 - Misran Misran; Ulfa Ichwan Yunus (Kelola: Journal of Islamic Education Management, 2020)
This study focuses on finding students' perceptions of online learning and to find supporting and inhibiting factors for the application of online learning during the Covid 19 pandemic. This study is a survey research. Data and information were collected through questionnaires and interviews. The population in this study were 147 students of Islamic education management in semester 4 and a sample of 79 students. Data were analyzed descriptively from questionnaires and interviews, compiling distribution tables and displaying data in diagrammatic form. The results showed that 49% of students could access learning well and 51% could not access online learning properly, 74.96% of students were able to learn independently and 25.04% were unable to learn independently, 48.61% of students stated that online learning effective and 51.38% stated that it was not effective, 78% of students stated that they were treated equally and 22% stated that they were treated unequally and 65.82% of students stated that there was good communication between lecturers and students and between students and students. The benefit of online learning, namely, flexibility in place and time, can be done independently, increased ability to operate technology, and easy access to communication. The inhibitings are unstable network connection, increased costs, less effective learning, and too many tasks.